Surgeon-performed intubation in awake patients utilising an anterior commissure laryngoscope with bougie: a retrospective case series. Issue 11 (31st October 2019) - Vasan, N R; Kosik, E; Collins, B; Clampitt, M
Abstract: Objective: This retrospective case series examined the outcomes of surgeon-performed intubation using the anterior commissure rigid laryngoscope and bougie in adults with a difficult airway, including awake patients. Methods: This study comprised a series of adult patients who underwent surgeon-performed intubation over a 10-year period. They were identified by a records search for the Current Procedural Terminology ('CPT') code 31500 – 'intubation by surgeon'. Results: Forty-nine intubations performed in the operating theatre were reviewed. Intubation performed by the surgeon using the rigid anterior commissure laryngoscope was successful in 47 of the cases (96 per cent). Over half of the patients had experienced failed intubation attempts with other methods by other providers prior to the surgeon performing direct laryngoscopy. Twenty intubations were performed without paralytics and with the patient awake. Conclusion: In properly selected adults who need an urgent, secure airway in the operating theatre, surgeon-performed anterior commissure laryngoscopic intubation using a bougie should be considered a safe, reliable procedure. In most cases, this procedure can be performed in selected patients whilst awake, with sedation.